Kadar Fenol Dan Antidiabetes Minuman Fungsional Kombinasi Teh Hitam Dan Singkil (Premna serrafolia) - DIAN FITRIARNI; Encik Eko Rifkowaty; Martanto Martanto; Nenengsih Verawaty; Dani Purwanto (Politeknik Negeri Lampung., 2022)
Diabetes is a degenerative disease that can arise due to unhealthy lifestyles. Until now there is no cure for this disease, but this disease can be minimized or prevented by consuming healthy food or functional food. Tea-based functional drinks have long been recognized and developed for their potential as an antidiabetic agent. One of them is by combining it with other ingredients like herbal plants. This study processed a black tea-based functional beverage combined with singkil leaves and stems. The purpose of this study was to determine the inhibitory enzymes and phenol content of black tea products combined with single leaf tea, and stem. Based on the analysis, all samples, both consisting of one composition or from the combination, generally have varying phenol levels. The highest inhibitory ability is possessed by tea samples which are categorized as strong, while the lowest inhibitory value is on black tea and singkil tea (THS2) with an IC50 value of 106,236. Based on the parameters of the observation of phenol levels, samples that have the highest phenol content are black tea (182,586 µg GEA / 100 g sample) while the sample with the lowest phenol content is tea (6,413 µg GEA / 100 g sample). All samples showed the ability to inhibit the alpha-glucosidase enzyme with a range between medium to strong. Phenol content is the only parameter used in this study. The overall sample showed the higher phenol levels have the enzyme inhibitory ability which tends to decrease. There may be a role from other indigenous secondary metabolite compounds that are not yet known from this study apart from compounds that arise due to the effects of the processing, such as. The results of the correlation test analysis showed a strong relationship between phenol contains and enzyme inhibitory properties (R = 0,765). Key Word: black tea, singkil, Premna seratifolia, antidiabetes, phenol